Problematika Penguasaan Kosakata Bahasa Jerman pada Siswa - Hasmawati, Hasmawati; Rijal, Syamsu; Mahmud, Siti Nurhalisah (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This research is aim to determine the problems and factors that influence students mastery of German vocabulary and the efforts made to overcome the problem of German vocabulary mastery of class XI students of SMKN 3 Takalar. This research is qualitative descriptive research. The population in this study were 156 class XI students of SMKN 3 Takalar who were studying German. The sample in this study were 65 class XI students of Computer Network Engineering at SMKN 3 Takalar and 1 German subject teacher. The sampling technique used was Random Sampling. The Data of this research was interviews, tests, and questionnaires. The results showed that the problems experienced by students were vocabulary pronunciation, memorizing and understanding the meaning of vocabulary. Factors that influence students mastery of German vocabulary are internal factors in the form of motivation, discipline, and student learning interest and external factors including teachers, facilities and infrastructure, and the environment. The efforts made by the teacher were to take an individual approach, provide motivation, provide additional practice assignments, hold consultation sessions outside of class hours, and use interactive media. The solution that students do is to study harder at home, set aside and organize time for practice, pay attention and listen to the teacher when explaining, use the internet and social media to learn GermanKeywords: Problems, Mastery of Vocabulary, German Language Learning